0358 Efficacy of a Stepped-care CBT-I Approach For Insomnia. (12th April 2019) - Cheng, Philip; Fellman-Couture, Cynthia; Atkinson, Rachel; Tonnu, Christine V; Moss, Kenneth; Drake, Christopher L
Abstract: Introduction: Digital cognitive behavioral therapy for insomnia (dCBT-I) has been shown to be effective, and confers the advantages of higher accessibility and affordability; however, tradeoffs include the loss of clinician support and the ability to personalize treatment. Furthermore, many individuals do not remit following dCBT-I, and thus may benefit from an increased dose of CBT-I. This study tested the efficacy of a stepped-care approach that combines dCBT-I (step 1) with face-to-face CBT-I (step 2). Methods: 261 individuals with insomnia (DSM-5 diagnostic criteria) were randomized into two conditions at step 1: dCBT-I (N=104), or an online sleep education control (N=157). Participants in the dCBT-I condition who did not remit (ISI>9) were further randomized to either face-to-face CBT-I (N=23) or sleep education (N=32). Insomnia (Insomnia Severity Scale) was assessed at baseline, post-step 1, and post-step 2. Results: Those who received stepped-care (dCBT-I to face-to-face CBT-I) achieved the same improvements in insomnia (pre-treatment ISI: 16.2, SD=4.9; post-treatment ISI: 7.5, SD=4.0) compared to those who remitted following only dCBT-I (pre-treatment ISI: 16.3, SD=3.9; post-treatment ISI: 7.5, SD=3.1). Furthermore, remission rates in the face-to-face CBT-I condition at step 2 (78.3%) was almost three-fold that of the control condition at step 2 (28.1%), indicating that the stepped-care condition produced higher rates of insomnia remission compared to dCBT-I alone. Conclusion: Preliminary evidence from this study provide suggest that a stepped-care approach that adds face-to-face CBT-I for non-remitters to dCBT-I is an efficacious model for insomnia treatment. Support (If Any): Support for this study was provided from the National Institute of Mental Health R56MH115150 awarded to Dr. Christopher Drake.